Rare earth polishing powder, preparation method thereof and polishing slurry
By enriching trivalent cerium in rare earth polishing powder on the surface layer and maintaining the body phase as tetravalent cerium, the problem of insufficient polishing activity and stability of rare earth polishing powder is solved, and the effect of efficient polishing rate and long service life is achieved.
Patent Information
- Application Number
- CN202310705329.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-17
AI Technical Summary
The polishing activity and polishing stability of rare earth polishing powder are poor, resulting in a reduced polishing rate and short service life.
Through the preparation method, trivalent cerium is enriched on the surface layer of rare earth polishing powder particles, keeping the body phase as tetravalent cerium, avoiding the existence of trivalent cerium in the body phase to destroy the structure, and optimizing it with hydrothermal treatment and calcining process to form excellent polishing performance rare earth polishing powder.
The polishing rate and service life of rare earth polishing powder are improved, and the polishing effect with low surface roughness and high structural stability is ensured.
Smart Images

Figure BDA0004285747910000101 
Figure BDA0004285747910000111 
Figure BDA0004285747910000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth polishing materials, in particular to rare earth polishing powder and a preparation method thereof, and polishing slurry. Background Art
[0002] Rare earth polishing powder is a polishing material with excellent performance. It has the advantages of moderate hardness, fast polishing rate, high polishing efficiency and clean operating environment. It is widely used in the polishing of silicon-containing materials such as flat glass, mobile phone cover glass, optical glass, liquid crystal display glass substrate and integrated circuit STI layer.
[0003] The polishing mechanism of rare earth polishing powder is chemical mechanical polishing. Its mechanical action is affected by the particle size, particle uniformity, particle morphology and particle hardness of the powder; while the chemical action is related to the composition, surface valence and structure of the powder, especially the surface valence has an important influence on the chemical action. In rare earth polishing powder, trivalent cerium can form Ce-O-Si bonds with the processed surface, enhance the interaction between the polishing powder particles and the processed surface, and weaken the Si-O-Si bonds, thereby improving the removal ability of the processed surface of the rare earth polishing powder. Therefore, trivalent cerium is the root cause of the chemical polishing activity of rare earth polishing powder, and increasing the trivalent cerium content is crucial to the preparation of high-performance rare earth polishing powder. Usually, cerium oxide in polishing powder exists in cubic fluorite phase, but when trivalent cerium exists in the bulk phase of polishing powder particles, oxygen vacancies will be formed, resulting in crystal defects and crystal deformation; especially when there is a large amount of trivalent cerium in the bulk phase, cerium oxide will form a hexagonal phase, which will destroy the structural stability of the polishing powder, resulting in the easy breakage of polishing powder particles during use, reduced polishing rate, and poor polishing stability. Summary of the invention
[0004] The main purpose of the present invention is to provide a rare earth polishing powder and a preparation method thereof, and a polishing slurry, so as to solve the problem that the rare earth polishing powder in the prior art has poor polishing activity and polishing stability.
[0005] In order to achieve the above object, according to one aspect of the present invention, a rare earth polishing powder is provided, the chemical formula of the rare earth polishing powder is Ce 1-x M x O y D z, wherein 0≤x≤0.6, 1.2≤y≤2.0, 0≤z≤0.9; the mass percentage of trivalent cerium in the total cerium in the rare earth polishing powder is ≤10%, and the mass percentage of trivalent cerium in the surface area of the rare earth polishing powder particles in the total cerium in the surface area of the rare earth polishing powder particles is ≥20%, wherein the surface area refers to the area 1 to 5 nm close to the surface of the rare earth polishing powder particles; M is selected from any one or more of transition metal elements, alkaline earth metal elements, aluminum elements, silicon elements, alkali metal elements and rare earth elements other than cerium, and D is selected from any one or more of fluorine, chlorine, phosphorus and sulfur.
[0006] Furthermore, the cerium oxide phase contained in the rare earth polishing powder is a cubic fluorite phase.
[0007] Furthermore, the mass percentage of the trivalent cerium in the surface region of the rare earth polishing powder particles in the total cerium in the surface region of the rare earth polishing powder particles is ≥25%.
[0008] Further, 0≤x≤0.4, preferably 1.5≤y≤2, preferably 0≤z≤0.6; preferably M is selected from any one or more of lanthanum, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, thulium, ytterbium, yttrium, zirconium, iron, magnesium, sodium, calcium, and silicon, and preferably D is fluorine and / or phosphorus.
[0009] Furthermore, the median particle size D of the rare earth polishing powder is 50 It is 0.01 to 5 μm, preferably 0.01 to 2 μm.
[0010] According to another aspect of the present invention, a method for preparing the aforementioned rare earth polishing powder is provided, the preparation method comprising: step S1, calcining a raw material including a cerium compound in an oxidizing atmosphere to obtain a calcined product; step S2, hydrothermally treating the calcined product in a solution to obtain rare earth polishing powder.
[0011] Furthermore, in the above step S1, the cerium-containing compound is selected from any one or more of cerium-containing carbonates, fluorocarbonates, oxalates, and hydroxides; the cerium-containing compound is preferably synthesized by any one or more of coprecipitation, sol-gel, microemulsion, combustion, and solid phase methods; the oxidizing atmosphere in step S1 is preferably oxygen or air; the calcination temperature in step S2 is preferably 300 to 1000°C, preferably 500 to 900°C; the calcination time is preferably 1 to 48 hours, preferably 1 to 24 hours.
[0012] Furthermore, in the above step S2, the temperature of the hydrothermal treatment is 100 to 250° C., preferably 120 to 200° C.; the time of the hydrothermal treatment is preferably 1 to 48 hours, preferably 3 to 24 hours.
[0013] Furthermore, in the above step S2, the solution is an aqueous solution with a pH value of 4 to 12, preferably an aqueous solution with a pH value of 5 to 10, and the pH value of the solution is preferably adjusted to be within the above range using sodium hydroxide and / or potassium hydroxide.
[0014] Furthermore, in the above step S2, the solution includes a reducing substance, and the reducing substance is selected from any one or more of ammonia water, hydrogen peroxide, potassium sulfite, potassium bisulfite, and potassium pyrosulfite. Preferably, the amount of the reducing substance is ≤ 30wt% of the mass of the roasting product.
[0015] According to another aspect of the present invention, there is provided a polishing slurry comprising rare earth polishing powder, a surfactant, a pH regulator and water, wherein the rare earth polishing powder is the rare earth polishing powder mentioned above.
[0016] Furthermore, in terms of mass percentage, the content of rare earth polishing powder in the above-mentioned polishing slurry is ≤20%, preferably ≤10%; the content of surfactant in the polishing slurry is preferably ≤5%, preferably ≤1%, and the surfactant is preferably selected from any one or more of sodium hexametaphosphate, sodium polyacrylate, sodium salt of maleic acid-acrylic acid copolymer, and sodium pyrophosphate; the pH value of the polishing slurry is preferably 4 to 10.
[0017] By applying the technical solution of the present invention, the bulk phase of the above rare earth polishing powder of the present application is basically tetravalent cerium, and trivalent cerium is enriched on the surface of the rare earth polishing powder particles. On the one hand, the surface enrichment of trivalent cerium is conducive to the formation of Ce-O-Si bonds, which can improve the polishing rate of the rare earth polishing powder; on the other hand, the bulk phase is basically tetravalent cerium, which avoids the presence of trivalent cerium in the bulk phase to destroy the face-centered cubic structure of cerium oxide, so that the structural stability of the rare earth polishing powder is relatively high, and thus it has an excellent polishing rate and service life, and can be processed to obtain a surface with extremely low roughness. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0019] As analyzed in the background technology, there is a problem in the prior art that rare earth polishing powder has poor polishing activity and polishing stability. In order to solve this problem, the present application provides a rare earth polishing powder and a preparation method thereof, and a polishing slurry.
[0020] In a typical embodiment of the present application, a rare earth polishing powder is provided, the chemical formula of the rare earth polishing powder is Ce 1-x M x O y D z, wherein 0≤x≤0.6, 1.2≤y≤2.0, 0≤z≤0.9; the mass percentage of trivalent cerium in the total cerium in the rare earth polishing powder is ≤10%, and the mass percentage of trivalent cerium in the surface area of the rare earth polishing powder particles in the total cerium in the surface area of the rare earth polishing powder particles is ≥20%, wherein the surface area refers to the area 1 to 5 nm close to the surface of the rare earth polishing powder particles; M is selected from any one or more of transition metal elements, alkaline earth metal elements, aluminum elements, silicon elements, alkali metal elements and rare earth elements other than cerium, and D is selected from any one or more of fluorine, chlorine, phosphorus and sulfur.
[0021] The bulk phase of the above rare earth polishing powder of the present application is basically tetravalent cerium, and trivalent cerium is enriched on the surface of the rare earth polishing powder particles. On the one hand, the surface enrichment of trivalent cerium is conducive to the formation of Ce-O-Si bonds, which can improve the polishing rate of the rare earth polishing powder; on the other hand, it helps to avoid the presence of trivalent cerium in the bulk phase to destroy the face-centered cubic structure of cerium oxide, so that the structural stability of the rare earth polishing powder is relatively high, and thus it has an excellent polishing rate and service life, and can be processed to obtain a surface with extremely low roughness.
[0022] The mass percentage of trivalent cerium in the rare earth polishing powder to the total cerium can be measured by the following method:
[0023] S1: The rare earth polishing powder is digested with concentrated phosphoric acid, and the cerium content measured by ammonium ferrous sulfate titration is a;
[0024] S2: The rare earth polishing powder is digested with a mixed acid of concentrated phosphoric acid and perchloric acid, and the cerium content measured by ammonium ferrous sulfate titration, ICP and other methods is b; and the mass percentage of trivalent cerium in the total cerium = (ba) / b×100%.
[0025] The mass percentage of the surface trivalent cerium content in the rare earth polishing powder to the total surface cerium can be tested by methods such as X-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR), electron energy loss spectroscopy (EELS), and Raman.
[0026] Taking X-ray photoelectron spectroscopy (XPS) as an example, the test spectrum of rare earth polishing powder has peaks near 880.7eV, 882.8eV, 885.7eV, 885.9eV, 898.1eV, 899.4eV, 901.2eV, 904.8eV, 908.1eV, and 916.9eV, and the mass percentage of trivalent cerium content on the surface to the total cerium on the surface = (A 880.7 +A 885.7 +A 899.4 +A 899.4 ) / (A 882.8 +A 889.5 +A 898.1 +A901.2 +A 908.1 +A 916.9 )×100%, where A is the integrated area of the peak.
[0027] Trivalent cerium is the fundamental reason for the chemical polishing activity of rare earth polishing powder. In some embodiments of the present application, the cerium oxide phase contained in the rare earth polishing powder is preferably a cubic fluorite phase, which can effectively avoid crystal defects (such as hexagonal phase) and crystal deformation caused by oxygen vacancies; thereby helping to improve the structural stability of the polishing powder, and then improve the polishing rate and polishing stability.
[0028] In order to further improve the polishing rate and service life of the rare earth polishing powder, the mass percentage of trivalent cerium in the surface area of the rare earth polishing powder particles is preferably ≥ 25% of the total cerium in the surface area of the rare earth polishing powder particles.
[0029] In one embodiment of the present application, preferably 0≤x≤0.4, preferably 1.5≤y≤2, preferably 0≤z≤0.6; preferably M is selected from any one or more of lanthanum, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, thulium, ytterbium, yttrium, zirconium, iron, magnesium, sodium, calcium, and silicon, and preferably D is fluorine and / or phosphorus.
[0030] The preferred values of x, y, and z above are helpful to improve the synergistic effect between the elements in the rare earth polishing powder. The preferred M is helpful to improve Ce to a certain extent. 3+ The content makes the rare earth polishing powder have polishing activity, polishing stability and a long service life.
[0031] In one embodiment of the present application, the median particle size D of the rare earth polishing powder is 50 It is 0.01 to 5 μm, preferably 0.01 to 2 μm.
[0032] The rare earth polishing powder with the above-mentioned particle size can be used for polishing various products on the market, especially the preferred small-particle rare earth polishing powder is more suitable for polishing precision products, and the surface roughness of the processed products is lower.
[0033] In another typical embodiment of the present application, a method for preparing the aforementioned rare earth polishing powder is provided, the preparation method comprising: step S1, calcining a raw material including a cerium compound in an oxidizing atmosphere to obtain a calcined product; step S2, hydrothermally treating the calcined product in a solution to obtain rare earth polishing powder.
[0034] Step S1 reduces the total trivalent cerium content of cerium oxide in the rare earth polishing powder, especially reduces the trivalent cerium content in the bulk phase, by calcining the cerium-containing compound in an oxidizing atmosphere; Step S2 increases the trivalent cerium content in the surface layer by hydrothermal treatment, so that the trivalent cerium is mainly enriched in the surface layer of the rare earth polishing powder particles. The hydrothermal treatment makes the system more dispersible, the reduction rate and the reduction effect better, and the obtained rare earth polishing powder particles are more uniform.
[0035] In one embodiment of the present application, in the above step S1, the cerium-containing compound is selected from any one or more of cerium-containing carbonates, fluorocarbonates, hydroxides, and fluoride oxides; the cerium-containing compound is preferably synthesized by any one or more of coprecipitation, sol-gel, microemulsion, combustion, and solid phase methods; the oxidizing atmosphere in step S1 is preferably oxygen or air; the calcination temperature in step S2 is preferably 300-1000°C, preferably 500-900°C; the calcination time is preferably 1-48h, preferably 1-24h.
[0036] The higher the oxygen concentration in the oxidizing atmosphere, the more it helps to improve the efficiency and effect of roasting. It is preferred to carry out the above roasting in oxygen for the best effect. It is preferred to carry out the above roasting in air to help reduce costs. The preferred roasting temperature and time are conducive to improving the efficiency and effect of roasting, thereby reducing the trivalent cerium content in the rare earth polishing powder phase as much as possible.
[0037] In some embodiments of the present application, in the above step S2, the temperature of the hydrothermal treatment is preferably 100-250°C, preferably 120-200°C; the time of the hydrothermal treatment is preferably 1-48 hours, preferably 3-24 hours, so as to help more trivalent cerium to be enriched in the surface layer of the rare earth polishing powder particles.
[0038] In some embodiments of the present application, in the above step S2, the solution is an aqueous solution with a pH value of 4 to 12, preferably an aqueous solution with a pH value of 5 to 10, and the pH value of the above solution is preferably adjusted to be within the above range using sodium hydroxide and / or potassium hydroxide.
[0039] Hydrothermally treating the calcined product in an aqueous solution with the above pH value is helpful to modify the rare earth polishing powder through the interaction between hydroxide ions and the surface layer of the rare earth polishing powder, thereby increasing the trivalent cerium content on the surface.
[0040] In some other embodiments of the present application, the above step S2 includes a reducing substance, and the reducing substance is selected from any one or more of ammonia water, hydrogen peroxide, potassium sulfite, potassium bisulfite, and potassium pyrosulfite. Preferably, the amount of the reducing substance is ≤ 30wt% of the mass of the roasting product.
[0041] Hydrothermal treatment in an aqueous solution with a reducing substance added thereto is helpful in reducing tetravalent cerium to trivalent cerium, thereby increasing the trivalent cerium content of the surface layer of the rare earth polishing powder.
[0042] In another typical embodiment of the present application, a polishing slurry is provided, comprising rare earth polishing powder, a surfactant, a pH adjuster and water, wherein the rare earth polishing powder is the rare earth polishing powder mentioned above.
[0043] The polishing slurry provided by the present invention has the advantages of the above-mentioned polishing powder and also has the characteristics of good suspension stability and excellent dispersion performance, thereby preventing the polishing rate and polishing accuracy from being reduced due to the problems of polishing powder sedimentation, agglomeration, and agglomeration during the polishing process.
[0044] In order to further improve the synergistic effect between the components of the rare earth polishing slurry, thereby improving the polishing activity and stability of the polishing slurry as much as possible, the content of rare earth polishing powder in the above-mentioned polishing slurry is preferably ≤20%, preferably ≤10%, in terms of mass percentage; the content of surfactant in the polishing slurry is preferably ≤5%, preferably ≤1%, and the surfactant is preferably selected from any one or more of sodium hexametaphosphate, sodium polyacrylate, sodium salt of maleic acid-acrylic acid copolymer, and sodium pyrophosphate; the pH value of the polishing slurry is preferably 4 to 10.
[0045] The polishing slurry provided by the invention is suitable for flat glass, mobile phone cover glass, optical glass, liquid crystal display glass, glass substrate, and integrated circuit fields.
[0046] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0047] Example 1
[0048] The cerium carbonate solid was calcined at 400°C in an oxygen atmosphere for 4 hours, and then the calcined product was obtained after crushing and classification. The calcined product was dispersed in deionized water, and the pH value was adjusted to 4 with ammonia water. The product was hydrothermally heated at 100°C for 48 hours, and then the hydrothermal product was filtered, washed, and dried to obtain CeO 2 Rare earth polishing powder.
[0049] Example 2
[0050] The cerium nitrate solution, lanthanum nitrate solution and ammonium bicarbonate solution were mixed in a stoichiometric ratio, and the precipitate was filtered, washed and dried to obtain a cerium-containing compound. After calcining it at 900°C in an oxygen atmosphere for 48 hours, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in deionized water, and the pH value was adjusted to 7 using a sodium hydroxide / ammonia mixed solution, and hydrothermaled at 120°C for 24 hours, and then the hydrothermal product was filtered, washed and dried to obtain a chemical formula of Ce 0.8 La0.2 O 1.9 Rare earth polishing powder.
[0051] Example 3
[0052] Cerium nitrate, praseodymium nitrate, lanthanum nitrate solution and ammonium bicarbonate solution were mixed in a stoichiometric ratio, and the precipitate was filtered, washed and dried to obtain a cerium-containing compound. After calcining it at 300°C in an oxygen atmosphere for 1 hour, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in deionized water, and the pH value was adjusted to 5 using a potassium hydroxide / ammonia mixed solution, and hydrothermaled at 150°C for 12 hours, and then the hydrothermal product was filtered, washed and dried to obtain a chemical formula of Ce 0.6 Pr 0.2 La 0.2 O 1.8 Rare earth polishing powder.
[0053] Example 4
[0054] The cerium nitrate solution and the ammonium bicarbonate solution were mixed in a stoichiometric ratio to obtain a precursor slurry, and then the precursor slurry was wet-fluorinated with hydrofluoric acid. The fluorinated product was filtered, washed, and dried to obtain a cerium-containing compound. After calcining it at 1000°C in an oxygen atmosphere for 24 hours, the calcined product was obtained after crushing and classification, and the product was dispersed in deionized water, and the pH value was adjusted to 6 with ammonia water, and hydrothermally heated at 180°C for 1 hour. After that, the hydrothermal product was filtered, washed, and dried to obtain a chemical formula of CeO 1.7 F 0.6 Rare earth polishing powder.
[0055] Example 5
[0056] Cerium chloride, lanthanum chloride, neodymium chloride solution and ammonium bicarbonate solution were mixed in a stoichiometric ratio, and the precipitate was filtered, washed and dried to obtain a cerium-containing compound. After calcining it at 700°C in an air atmosphere for 12 hours, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in deionized water, and the pH value was adjusted to 8 with sodium hydroxide, and hydrothermaled at 200°C for 3 hours, and then the hydrothermal product was filtered, washed and dried to obtain a chemical formula of Ce 0.9 La 0.05 Nd 0.05 O 1.95 Rare earth polishing powder.
[0057] Example 6
[0058] Cerium oxalate, lanthanum oxalate and ammonium bicarbonate solution were mixed in a stoichiometric ratio to obtain a precursor slurry, which was then wet-fluorinated with hydrofluoric acid. The fluorinated product was filtered, washed and dried to obtain a cerium-containing compound. It was calcined at 500°C in an air atmosphere for 6 hours, and then crushed and classified to obtain a calcined product, which was dispersed in deionized water, and the pH value was adjusted to 10 with potassium hydroxide, and then hydrothermally heated at 220°C for 8 hours. The hydrothermal product was then filtered, washed and dried to obtain a chemical formula of Ce. 0.4 La 0.6 O 1.25 F 0.9 Rare earth polishing powder.
[0059] Example 7
[0060] The cerium nitrate solution and ammonia water were mixed in a stoichiometric ratio, and then the precipitate was filtered, washed, and dried to obtain a cerium-containing compound. After calcining it at 600°C in an oxygen atmosphere for 8 hours, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in deionized water, and the pH value was adjusted to 12 using an ammonia water / sodium hydroxide mixed solution, and hydrothermaled at 250°C for 15 hours, and then the hydrothermal product was filtered, washed, and dried to obtain a chemical formula of CeO 2 Rare earth polishing powder.
[0061] Example 8
[0062] Cerium nitrate solution, ammonia water and sodium hexametaphosphate were mixed in a stoichiometric ratio, and the precipitate was filtered, washed and dried to obtain a cerium-containing compound. After calcining it at 600°C in an oxygen atmosphere for 8 hours, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in deionized water, and the pH value was adjusted to 12 with a mixed solution of ammonia water / sodium hydroxide, and hydrothermaled at 250°C for 15 hours. After that, the hydrothermal product was filtered, washed and dried to obtain a chemical formula of Ce 0.9 P 0.1 O 2 Rare earth polishing powder.
[0063] Example 9
[0064] The difference from Example 7 is that ammonia water is used to adjust the pH value to 4, and finally CeO 2 Rare earth polishing powder.
[0065] Example 10
[0066] The difference from Example 7 is that ammonia water is used to adjust the pH value to 5, and finally CeO 2 Rare earth polishing powder.
[0067] Embodiment 11
[0068] The difference from Example 7 is that ammonia water is used to adjust the pH value to 6, and finally CeO 2 Rare earth polishing powder.
[0069] Example 12
[0070] The difference from Example 7 is that ammonia water is used to adjust the pH value to 7, and finally CeO 2 Rare earth polishing powder.
[0071] Example 13
[0072] The difference from Example 7 is that ammonia water is used to adjust the pH value to 8, and finally CeO 2 Rare earth polishing powder.
[0073] Embodiment 14
[0074] The difference from Example 7 is that ammonia water is used to adjust the pH value to 9, and finally CeO 2 Rare earth polishing powder.
[0075] Embodiment 15
[0076] The difference from Example 7 is that ammonia water is used to adjust the pH value to 10, and finally CeO 2 Rare earth polishing powder.
[0077] Example 16
[0078] The difference from Example 7 is that ammonia water is used to adjust the pH value to 11, and finally CeO 2 Rare earth polishing powder.
[0079] Embodiment 17
[0080] The cerium carbonate solid was calcined at 400°C in an oxygen atmosphere for 4 hours, and then the calcined product was obtained after crushing and classification. The calcined product was dispersed in an ammonia solution and hydrothermally heated at 100°C for 48 hours. The hydrothermal product was then filtered, washed, and dried to obtain a cerium carbonate having a chemical formula of CeO 2 Rare earth polishing powder.
[0081] Embodiment 18
[0082] The cerium nitrate solution, lanthanum nitrate solution and ammonium bicarbonate solution were mixed in a stoichiometric ratio, and the precipitate was filtered, washed and dried to obtain a cerium-containing compound. After calcining it at 900°C in an oxygen atmosphere for 48 hours, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in a hydrogen peroxide solution and hydrothermally heated at 120°C for 24 hours. The hydrothermal product was then filtered, washed and dried to obtain a compound with a chemical formula of Ce. 0.5 La 0.5 O 1.75 Rare earth polishing powder.
[0083] Embodiment 19
[0084] Cerium nitrate, praseodymium nitrate, lanthanum nitrate solution and ammonium bicarbonate solution were mixed in a stoichiometric ratio, and the precipitate was filtered, washed and dried to obtain a cerium-containing compound. After calcining it at 300°C in an oxygen atmosphere for 1 hour, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in an ammonia solution and hydrothermally heated at 150°C for 12 hours. The hydrothermal product was then filtered, washed and dried to obtain a compound with a chemical formula of Ce. 0.8 Pr 0.1 La 0.1 O 1.9 Rare earth polishing powder.
[0085] Embodiment 20
[0086] The cerium nitrate solution and the ammonium bicarbonate solution are mixed in a stoichiometric ratio to obtain a precursor slurry, and then the precursor slurry is wet-fluorinated with hydrofluoric acid. The fluorinated product is filtered, washed, and dried to obtain a cerium-containing compound. After calcining it at 1000°C in an oxygen atmosphere for 24 hours, the calcined product is obtained after crushing and classification, and the calcined product is dispersed in hydrogen peroxide and hydrothermally heated at 180°C for 1 hour. The hydrothermal product is then filtered, washed, and dried to obtain a compound with the chemical formula CeO 1.7 F 0.6 Rare earth polishing powder.
[0087] Embodiment 21
[0088] Cerium chloride, lanthanum chloride, neodymium chloride solution and ammonium bicarbonate solution were mixed in a stoichiometric ratio, and the precipitate was filtered, washed and dried to obtain a cerium-containing compound. After calcining it at 700°C in an air atmosphere for 12 hours, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in ammonia water and hydrothermally heated at 200°C for 3 hours. The hydrothermal product was then filtered, washed and dried to obtain a compound with a chemical formula of Ce. 0.4 La 0.3 Nd 0.3 O 1.7 Rare earth polishing powder.
[0089] Embodiment 22
[0090] Cerium oxalate, lanthanum oxalate and ammonium bicarbonate solution are mixed in a stoichiometric ratio to obtain a precursor slurry, which is then wet-fluorinated with hydrofluoric acid. The fluorinated product is filtered, washed and dried to obtain a cerium-containing compound. It is calcined at 500°C in an air atmosphere for 6 hours, crushed and classified to obtain a calcined product, which is dispersed in a sodium pyrosulfite solution and hydrothermally heated at 220°C for 8 hours. The hydrothermal product is then filtered, washed and dried to obtain a compound with the chemical formula Ce. 0.9 La 0.1 O 1.5 F0.9 Rare earth polishing powder.
[0091] Embodiment 23
[0092] The cerium nitrate solution and ammonia water were mixed in a stoichiometric ratio, and then the precipitate was filtered, washed, and dried to obtain a cerium-containing compound. After calcining it at 600°C in an oxygen atmosphere for 8 hours, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in a mixed solution of ammonia water / hydrogen peroxide and hydrothermally heated at 250°C for 15 hours. After that, the hydrothermal product was filtered, washed, and dried to obtain a compound with the chemical formula CeO 2 Rare earth polishing powder.
[0093] Embodiment 24
[0094] Cerium nitrate solution, ammonia water and sodium hexametaphosphate were mixed in a stoichiometric ratio, and the precipitate was filtered, washed and dried to obtain a cerium-containing compound. After calcining it at 600°C in an oxygen atmosphere for 8 hours, the calcined product was obtained after crushing and classification, and the calcined product was dispersed in a mixed solution of ammonia water / hydrogen peroxide and hydrothermaled at 250°C for 15 hours, and then the hydrothermal product was filtered, washed and dried to obtain a compound with a chemical formula of Ce. 0.9 P 0.1 O 2 Rare earth polishing powder.
[0095] Embodiment 25
[0096] The difference from Example 23 is that after crushing and classification, the calcined product is obtained, which is dispersed in a mixed solution of ammonia water / hydrogen peroxide and hydrothermaled at 100°C for 15 hours to finally obtain a product with the chemical formula CeO 2 Rare earth polishing powder.
[0097] Embodiment 26
[0098] The difference from Example 23 is that after crushing and classification, the calcined product is obtained, which is dispersed in a mixed solution of ammonia water / hydrogen peroxide and hydrothermaled at 120°C for 15 hours to finally obtain a product with the chemical formula CeO 2 Rare earth polishing powder.
[0099] Embodiment 27
[0100] The difference from Example 23 is that after crushing and classification, the calcined product is obtained, which is dispersed in a mixed solution of ammonia water / hydrogen peroxide and hydrothermaled at 150°C for 15h to finally obtain a product with the chemical formula CeO 2 Rare earth polishing powder.
[0101] Embodiment 28
[0102] The difference from Example 23 is that after crushing and classification, the calcined product is obtained, which is dispersed in a mixed solution of ammonia water / hydrogen peroxide and hydrothermaled at 180°C for 15 hours to finally obtain a product with the chemical formula CeO 2 Rare earth polishing powder.
[0103] Embodiment 29
[0104] The difference from Example 23 is that after crushing and classification, the calcined product is obtained, which is dispersed in a mixed solution of ammonia water / hydrogen peroxide and hydrothermaled at 200°C for 15 hours to finally obtain a product with the chemical formula CeO 2 Rare earth polishing powder.
[0105] Embodiment 30
[0106] The difference from Example 23 is that after crushing and classification, the calcined product is obtained, which is dispersed in a mixed solution of ammonia water / hydrogen peroxide and hydrothermaled at 220°C for 15 hours to finally obtain a product with the chemical formula CeO 2 Rare earth polishing powder.
[0107] Comparative Example 1
[0108] The cerium nitrate solution and the ammonium bicarbonate solution were mixed in a stoichiometric ratio to obtain a precursor slurry, and then the precursor slurry was wet-fluorinated with hydrofluoric acid. The fluorinated slurry was filtered, washed, and dried to obtain a cerium-containing compound. After calcining it at 1000°C in a hydrogen atmosphere for 24 hours, it was crushed and classified to obtain a compound with the chemical formula CeO 1.7 F 0.6 Rare earth polishing powder.
[0109] Comparative Example 2
[0110] The cerium nitrate solution and ammonia water are mixed in a stoichiometric ratio, and then the precipitate is filtered, washed, and dried to obtain a cerium-containing compound. After calcining it at 600°C in an oxygen atmosphere for 8 hours, it is crushed and classified to obtain a cerium compound with a chemical formula of CeO 2 Rare earth polishing powder.
[0111] The D50 particle size of the rare earth polishing powder obtained in Examples 1 to 30 and Comparative Examples 1 and 2 was measured by a dynamic laser particle size analyzer, the trivalent cerium content in the surface layer was measured by XPS, and the content of trivalent cerium in the total cerium was measured by EDTA titration. The test data and the chemical formula of the rare earth polishing powder are listed in Table 1.
[0112] Application Examples 1 to 30, Application Comparative Examples 1 and 2
[0113] Take the rare earth polishing powder prepared in Examples 1 to 30, Comparative Examples 1 and 2 respectively, disperse them in deionized water, add sodium hexametaphosphate as a surfactant, and disperse them mechanically at high speed (2000rpm) for 30 minutes to prepare a polishing slurry. Use the prepared rare earth polishing slurry to polish K9 glass (80mm×100mm×0.5mm) or oxidized silicon wafers (4 inches in diameter), with a polishing pressure of 4.95psi, a polishing disc and a stage with rotation speeds of 45 and 15rpm / min, respectively, and a polishing time of 20min. The polishing rate is measured, and the non-contact surface profiler measures the surface roughness Sa of the glass before and after polishing. The polishing slurry is recycled, and the number of cycles is when the polishing rate is reduced to 80% of the initial polishing rate, and the test results are listed in Table 2.
[0114] Table 1
[0115]
[0116]
[0117] Table 2
[0118]
[0119]
[0120] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0121] The bulk phase of the above rare earth polishing powder of the present application is basically tetravalent cerium, and trivalent cerium is enriched on the surface of the rare earth polishing powder particles. On the one hand, the surface enrichment of trivalent cerium is conducive to the formation of Ce-O-Si bonds, which can improve the polishing rate of the rare earth polishing powder; on the other hand, it helps to avoid the presence of trivalent cerium in the bulk phase to destroy the face-centered cubic structure of cerium oxide, so that the structural stability of the rare earth polishing powder is relatively high, and thus it has an excellent polishing rate and service life, and can be processed to obtain a surface with extremely low roughness.
[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A rare earth polishing powder, characterized in that: The chemical formula of the rare earth polishing powder is Ce 1-x M x O y D z , wherein 0≤x≤0.6, 1.2≤y≤2.0, 0≤z≤0.9; the mass percentage of trivalent cerium in the total cerium in the rare earth polishing powder is ≤10%, and the mass percentage of trivalent cerium in the surface area of the rare earth polishing powder particles in the total cerium in the surface area of the rare earth polishing powder particles is ≥20%, wherein the surface area refers to the area 1 to 5 nm close to the surface of the rare earth polishing powder particles; M is selected from any one or more of transition metal elements, alkaline earth metal elements, aluminum elements, silicon elements, alkali metal elements and rare earth elements except cerium, and D is selected from any one or more of fluorine, chlorine, phosphorus and sulfur.
2. A rare earth polishing powder according to claim 1, characterized in that: The cerium oxide phase contained in the rare earth polishing powder is a cubic fluorite phase.
3. The rare earth polishing powder according to claim 1 or 2, characterized in that: The mass percentage of the trivalent cerium in the surface layer of the rare earth polishing powder particles in the total cerium in the surface layer of the rare earth polishing powder particles is ≥25%.
4. The rare earth polishing powder according to any one of claims 1 to 3, characterized in that 0≤x≤0.4, preferably 1.5≤y≤2, preferably 0≤z≤0.6; preferably, M is selected from any one or more of lanthanum, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, thulium, ytterbium, yttrium, zirconium, iron, magnesium, sodium, calcium, and silicon, and preferably, D is fluorine and / or phosphorus.
5. The rare earth polishing powder according to any one of claims 1 to 4, characterized in that: The median particle size D of the rare earth polishing powder 50 It is 0.01 to 5 μm, preferably 0.01 to 2 μm.
6. A method for preparing the rare earth polishing powder according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Step S1, calcining a raw material including a cerium compound in an oxidizing atmosphere to obtain a calcined product; Step S2, subjecting the calcined product to hydrothermal treatment in a solution to obtain the rare earth polishing powder.
7. The preparation method according to claim 6, characterized in that: In step S1, the cerium-containing compound is selected from any one or more of cerium-containing carbonates, fluorocarbonates, oxalates, and hydroxides; the cerium-containing compound is preferably synthesized by any one or more of a coprecipitation method, a sol-gel method, a microemulsion method, a combustion method, and a solid phase method; Preferably, the oxidizing atmosphere in step S1 is oxygen or air; Preferably, the calcination temperature in step S2 is 300-1000° C., preferably 500-900° C.; preferably, the calcination time is 1-48 h, preferably 1-24 h.
8. The preparation method according to claim 6 or 7, characterized in that: In the step S2, the temperature of the hydrothermal treatment is 100 to 250°C, preferably 120 to 200°C; the time of the hydrothermal treatment is preferably 1 to 48 hours, preferably 3 to 24 hours.
9. The preparation method according to any one of claims 6 to 8, characterized in that: In step S2, the solution is an aqueous solution with a pH value of 4 to 12, preferably an aqueous solution with a pH value of 5 to 10, and the pH value of the solution is preferably adjusted to be within the above range using sodium hydroxide and / or potassium hydroxide.
10. The preparation method according to any one of claims 6 to 8, characterized in that: In step S2, the solution includes a reducing substance, and the reducing substance is selected from any one or more of ammonia water, hydrogen peroxide, potassium sulfite, potassium bisulfite, and potassium pyrosulfite. Preferably, the amount of the reducing substance is ≤ 30wt% of the mass of the roasting product.
11. A polishing slurry comprising rare earth polishing powder, a surfactant, a pH regulator and water, characterized in that: The rare earth polishing powder is the rare earth polishing powder according to any one of claims 1 to 5.
12. The polishing slurry according to claim 11, characterized in that In terms of mass percentage, the content of the rare earth polishing powder in the polishing slurry is ≤20%, preferably ≤10%; preferably, the content of the surfactant in the polishing slurry is ≤5%, preferably ≤1%, and preferably, the surfactant is selected from any one or more of sodium hexametaphosphate, sodium polyacrylate, sodium salt of maleic acid-acrylic acid copolymer, and sodium pyrophosphate; preferably, the pH value of the polishing slurry is 4 to 10.
